Unemployed people in search for a job: Exploring the antecedents of job-seeking success - Galesić, Mirta (Array, 2006)
Our current understanding of job-seeking behavior is mostly based on the findings coming from developed countries, in particular the US. This paper seeks to verify and extend the findings to different socio-economic contexts. Our longitudinal survey of Croatian unemployed persons (N = 1138) examined antecedents of job-seeking behavior and factors contributing to (re)employment. Building on previous work, we devised a hypothetical model of job-seeking antecedents that includes a series of demographic, personal and situational variables. These variables were posited to influence the job-seeking behavior, which, in turn, affects reemployment. The participants were surveyed in 2003, and their employment status was checked in 2004 and 2005. Regression analyses proved most of the hypothesized relations. Apart from the demographic variables, financial pressures, deprivation of the latent benefits of employment, social support, and both mental and physical health significantly influenced the job-seeking intensity, whereas only physical health was significantly related to reemployment. The job-seeking intensity significantly correlated with reemployment and contributed to the regression equation above and beyond the control and predictor variables. We discuss the results in light of the previous findings and indicate their theoretical and practical implications.